Evaluation of Policy-based Initiatives’ Impact on Indian Tribal Populations: Current Circumstances and Potential for Development - Acharya Balkrishna; Neha Kaushik; Neelam Rawat Dabhade; Vedpriya Arya (An Overview of Literature, Language and Education Research Vol. 10, 2025)
Anomalies, complications and difficulties at policy, planning, implementation, administration levels, allied problems with both the educational and healthcare systems, content, curriculum, medium of instruction, pedagogy, supervision, monitoring, teacher/colleague interaction related hitches, social, economic, and cultural issues are some of the reasons why tribal communities continue to lag behind the general population in health and education. To address various issues along with other allied variables, several social and government programmes have been witnessed over time to improve the general living standard of tribes in India. National and International scholarship schemes for higher education of ST Students, Pre-Matric Scholarship Schemes and Post-Matric Scholarship (PMS) Schemes are among them. The government of India also has achieved a number of milestones in the area of tribal health by launching various schemes and devising different portals such as National Tribal Health Portal, The Sickle Cell Disease Support (SCD) Corner; ALEKH: A Learning Endeavour for Knowledge in Healthcare and, The Tribal Health Compendium etc. The fact that just launching programmes and schemes is not a panacea for the scourge of illiteracy among tribal masses. The benefits of these programmes have only recently reached them. The tribal population’s lack of awareness of these plans, the distinctive character of their houses, and administrative officials’ disinterest in implementing these schemes and programmes are barriers to ST education and health.